Sedekah Jelantah: Sebuah Inisiatif untuk Mempromosikan Sistem “Waste Management” dan untuk Menciptakan Komunitas Mandiri melalui Biofuel - Amelia Naim Indrawijaya; Agus Loekman; Gusti Fauzi Maulana Gafli; Fariz Fadhillah; Cecilia Astrid Maharani; Fajar Rachmanto; Rezly Eskarlita Syauta (Jurnal Pengabdian Pada Masyarakat, 2020)
WASTE COOKING OIL DONATION: AN INITIATIVE TO PROMOTE “WASTE MANAGEMENT” SYSTEMS AND TO CREATE AN INDEPENDENT COMMUNITY THROUGH BIOFUELS. The supply of fossil fuels has been running low, and fossil fuel needs cannot be met by fossil fuels. Indonesia is in dire need of a substitute energy source that is not only available sustainably but also to produce renewable energy. One alternative is energy based on used cooking oil. This idea is a very interesting idea because used cooking oil can be a very promising source of fuel. Unfortunately all this used cooking oil has not been utilized properly, even polluting the soil and water. The purpose of this community program is to communicate and socialize the importance of distributing used cooking oil to become a renewable energy source, thus preventing pollution problems due to waste cooking oil disposal. This community development is carried out by developing a system within the community to ensure the collection of used cooking oil for the sustainability of the renewable energy program as an alternative resource for energy that is environmentally friendly. This initiative was given the name Sedekah Jelantah program.